2002
DOI: 10.1136/sti.78.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing STD incidence and increasing condom use among Chinese sex workers following a short term intervention: a prospective cohort study

Abstract: Objective: To describe the impact of a repeating behavioural intervention focused on preventive education and provision of STD testing and treatment services to female sex workers. Methods: A prospective cohort study of 966 sex workers (first of its kind in China) was conducted in Guangzhou from March 1998 to October 1999. At each visit information was collected on sexual behaviour, condom use and knowledge about HIV transmission and condom use, education was given, STD were diagnosed, and treatment was provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 10 publications
1
35
2
Order By: Relevance
“…The modified model produced only one latent construct (i.e., knowledge) that had direct effect on condom use. In this regard, there have been previous studies that demonstrate that increase in knowledge is significantly associated with improved use of condom among university students [8][9][10][11] .In contrast, there have been findings that contradict the findings in the current study; that is, increase in…”
Section: African Journal Of Reproductive Health September 2017; 21 (3)contrasting
confidence: 56%
See 1 more Smart Citation
“…The modified model produced only one latent construct (i.e., knowledge) that had direct effect on condom use. In this regard, there have been previous studies that demonstrate that increase in knowledge is significantly associated with improved use of condom among university students [8][9][10][11] .In contrast, there have been findings that contradict the findings in the current study; that is, increase in…”
Section: African Journal Of Reproductive Health September 2017; 21 (3)contrasting
confidence: 56%
“…One of the basic reasons to analyse HIV/AIDS knowledge is to examine its direct linkage to improve the chances of self-protection (e.g., enhanced knowledge allows for consistent and proper use of condoms) [7][8][9][10][11] . Although this may be true, empirical evidences suggest mixed reports regarding the level of HIV/AIDS knowledge among university students.…”
Section: African Journal Of Reproductive Health September 2017; 21 (3)mentioning
confidence: 99%
“…In Zaire (Laga et al 1994) and Nairobi (Ngugi et al 1988(Ngugi et al , 1996 they examined the effect on incident HIV while in Peru (Sanchez et al 2003) and China (Ma et al 2002) the primary outcome was incident STIs. Only the Chinese cohort reported the loss to follow-up, which was 50%.…”
Section: Treatment Of Bacterial Sexually Transmitted Infections Combimentioning
confidence: 99%
“…The overall follow-up rates in our study (73.1% of FSWs at 6 months and 50.2% of FSWs at 12 months) are far better than those for the other FSW cohort in China, which was able to follow 53% at approximately 6 months [21]. Higher FSW retention rates in our study may be partly attributed to the gains from mobile phone use, such as text message appointment reminders and health behavior promotion.…”
Section: Discussionmentioning
confidence: 52%
“…One study reported approaching 13 785 FSWs but enrolling only 977 (7.1%), [18] making our enrollment rate of 49.3% (3597 of 7297) a substantial improvement. Despite the importance of better understanding FSW STI and HIV needs and testing interventions, this is, to our knowledge, only the second Chinese FSW cohort described in the English literature [21]. This study is also important because it provides a more robust understanding of the sexual risk and social composition of FSWs at low-tier sex venues, a group that has been difficult to accurately study in China [11] and that is less well represented in current surveillance and intervention programs in China.…”
Section: Discussionmentioning
confidence: 99%